Infraestructura física y social y su impacto en el desarrollo económico de América Latina, período 2010 - 2019. - Jiménez Shinín, Ana Karen (2023)
The main objective of this research was to determine the impact of physical and social infrastructure on the economic development of Latin America in the period 2010 – 2019, for which a bibliographic and statistical analysis of the variables used in the model was carried out. Specifically, a panel data model was development for 14 countries. Through the Hausman test, it was possible to determine that the random effects model is the most appropriate; in addition to this, the cointegration test yielded results for the application of a VAR model, which uses tests such as Granger causality, impulse response, and variance decomposition, results very close to those described in the economic literature was obtained. With the information provided by the model, the social and physical infrastructure have a direct relationship with economic development. Still, this effect is more marked in the long term since school enrollment causes development to increase by 14.91% and the number of doctors raises it by 4.62%.